2006
DOI: 10.1161/01.atv.0000223901.08459.57
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Antimicrobial Peptide LL-37 in Human Atherosclerosis

Abstract: Objective-Antimicrobial peptides are effector molecules of the innate immune system. To understand the function of vascular innate immunity in atherosclerosis, we investigated the role of LL-37, a cathelicidin antimicrobial peptide, in the disease process. Methods and Results-Using real-time polymerase chain reaction, we found a 6-fold increase in human cationic antimicrobial protein 18/LL-37 transcript in human atherosclerotic lesions compared with normal arteries. Immunohistochemical analysis of atherosclero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
110
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(119 citation statements)
references
References 50 publications
8
110
0
1
Order By: Relevance
“…LL-37 has been found in infiltrating macrophages and in some endothelial cells (ECs) in atherosclerotic lesions 14,15) . It may induce ICAM-1 and MCP-1 expression in cultured HUVECs 14) , and induce apoptosis of cultured VSMCs, which is known to be implicated in plaque rupture 15) .…”
Section: Human Neutrophil Peptide 1-3 and Acute Myocardial Infarctionmentioning
confidence: 99%
See 1 more Smart Citation
“…LL-37 has been found in infiltrating macrophages and in some endothelial cells (ECs) in atherosclerotic lesions 14,15) . It may induce ICAM-1 and MCP-1 expression in cultured HUVECs 14) , and induce apoptosis of cultured VSMCs, which is known to be implicated in plaque rupture 15) .…”
Section: Human Neutrophil Peptide 1-3 and Acute Myocardial Infarctionmentioning
confidence: 99%
“…It may induce ICAM-1 and MCP-1 expression in cultured HUVECs 14) , and induce apoptosis of cultured VSMCs, which is known to be implicated in plaque rupture 15) . PR-39, a cathelicidin family member in pigs, has been reported to play cardioprotective roles, such as limiting infarction size and proangiogenic function 16,17) ; however, there is lack of sequence and structural similarities between LL-37 and PR-39 16) .…”
Section: Human Neutrophil Peptide 1-3 and Acute Myocardial Infarctionmentioning
confidence: 99%
“…In addition, FPRL1 has been implicated in the tube formation of HUVECs stimulated with LL-37 [13,23]. Hence, we attempted to determine whether F2L alters tube formation in the LL-37-treated HUVECs.…”
Section: The Stimulation Of Huvecs With F2l Inhibits Angiogenesismentioning
confidence: 99%
“…The association observed between the MLR and LL-37 is not surprising, as monocytes and derived macrophages are known to release LL-37 in atherosclerotic lesions [98,101].…”
Section: The Monocyte-to-lymphocyte Ratio: a Pni Correlate In Stable Cadmentioning
confidence: 87%
“…It can be expressed by monocytes/macrophages, neutrophils, natural killer cells and epithel cells [98][99][100]. It was found that LL-37 could be produced also by macrophages in atherosclerotic lesions [98,101].…”
Section: Blood Plasma Inflammatory Factors In Cadmentioning
confidence: 99%